Benchmarking Visit to UTM and UTEM for Open & Distance Learning (ODL) Program Development - Mohd Khairul Bazli, Mohd Aziz (Pusat Sains Matematik (PSM), 2024)
A distinguished delegation from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently completed a successful benchmarking visit to Universiti Teknologi Malaysia (UTM) and Universiti Teknikal Malaysia Melaka (UTeM) from May 11 to May 14, 2024. The visit was led by Dr. Zulkhibri Bin Ismail @ Mustofa, Deputy Dean (Research & Postgraduate Studies), and included key academic leaders from UMPSA: Ts. Dr. Azlyna Binti Senawi, Head of Program (Postgraduates), Dr. Norhafizah Binti Md Sarif, Head of Program (Service Mathematics), Dr. Amirul Aizad Bin Ahmad Fuad, and Dr. Mohd Khairul Bazli Bin Mohd Aziz.